EPIPACTIS × SCHMALHAUSENII K. RICHT. (ORCHIDACEAE), A NEWLY IDENTIFED TAXON IN ROMANIAN FLORA - Remus DULUGEAC; Mihai BOBOCEA; Culiţă SÎRBU; Adrian OPREA (Journal of Plant Development, 2019)
The authors reports the presence in the Romanian wild flora of the nothospecies Epipactis × schmalhausenii. This taxon of hybrid origin (Epipactis atrorubens × E. helleborine subsp. helleborine) was recently identified, together with the two genitors, on some limestone mountains in the Romanan Eastern Carpathians (Bistriţei Mountains; Ceahlău Mountains; Hășmaș Mountains), as well as in Southern Carpathians (Bucegi Mountains). Although, this one is relatively widespread in other European countries, even in Kazakhstan (Central Asia), nothosp. Epipactis × schmalhausenii has not been reported in botanical literature of Romania, until now.